Productivity, Carcass Traits, and Meat Quality of Local Lambs Fed with Carica pubescens Seeds Meal - Idayanti, R. W.; Istianah, I.; Putri, S. N. H.; Fauziah, A. N.; Murniyadi, Z.; Esnadewi, L. G.; Purbowati, E.; Arifin, M.; Purnomoadi, A. (Tropical Animal Science Journal, 2024)
This study aimed to determine the effect of substituting agricultural by-products of Carica pubescens seeds meal with some concentrates on productivity, carcass characteristics, and meat quality of local lambs. Eighteen male thin-tailed lambs with an average initial body weight of 10.68 ± 1.3 kg (3-4 months old) were treated with a completely randomized design for ten weeks. The feed ingredients were C. pubescens, Pakchong grass (PG), and concentrate (K). Feed ingredients were prepared into complete feed with a balance of forage and concentrate 40:60% with three treatments, namely: T1= 40% PG + 55% K + 5% C. pubescens; T2= 40% PG + 47.5% K + 12.5% C. pubescens; and T3= 40% RG + 40% K + 20% C. pubescens. The use of 20% C. pubescens-treated lambs was statistically different (p